LEGAL REVIEW OF THE NUCLEAR ENERGY REGIME - Donni Taufiq; Amil Mardha (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2020)
During the second term of his administration, President Joko Widodo is planning to launch the Omnibus Law as solution to revise hundreds of conflicting articles in numerous existing laws and regulations simultaneously, not only at the central government level but also at the regional levels. This is a good opportunity for the Indonesian nuclear community to rearrange its nuclear energy regime, which can be seen, especially in the field of the energy sector, does not make significant progress. In the upcoming policy, more parties must be involved in the utilization of nuclear energy, especially in terms of financing and investment, for benefits to the greatest prosperity of the Indonesian people.